Root biomass and cumulative yield increase with mowing height in Festuca pratensis irrespective of Epichloë symbiosis - Laihonen Miika; Rainio Kalle; Birge Traci; Saikkonen Kari; Helander Marjo; Fuchs Benjamin (Nature Publishing Group, 2025)
Increasing agricultural soil carbon sequestration without compromising the productivity of the land is a key challenge in global climate change mitigation. The carbon mitigation potential of grass-based agriculture is particularly high because grasslands represent 70% of the world's agricultural area. The root systems of grasses transfer large amounts of carbon to below-ground storage, and the carbon allocation to the roots is dependent on the grasses' photosynthesizing shoot biomass. In a common-garden experiment, Festuca pratensis was used as a model species to study how mowing and weed control practices of perennial cool-season fodder grasses affect total yield and root biomass. Additionally, grass-associated Epichloë endophytes and soil residual glyphosate were tested for their effect on the total yield and root biomass alone or in interaction with mowing. The results demonstrate that elevating the cutting height increases both cumulative yield and root biomass in F. pratensis. Endophyte symbiosis increased the total yield, while glyphosate-based herbicide residues in the soil decreased the root biomass, which indicates a reduction of soil bound carbon sequestration. The findings demonstrate that carbon sequestration and yield quantities on farmed grasslands may significantly be improved by optimizing strategies for the use of plant protection products and adjustment of mowing intensity.